Endoscopic reversal of roux-en-Y gastric bypass prevents worsening of nutritional outcomes in patients with severe malnutrition - Dutta, Nirjhar; Scott, Adam W.; Marka, Nicholas A.; Wise, Eric S.; Amateau, Stuart K. (Frontiers in Gastroenterology, 2023)
Roux-en-Y gastric bypass (RYGB) can precipitate protein-calorie malnutrition and micronutrient deficiencies. Sonographically guided endoscopic reversal (ER) via deployment of a stent from the gastric pouch to the remnant stomach in RYGB anatomy has emerged as a novel option for increasing both intestinal transit time and absorptive surface area. In this investigation, short-term nutritional outcomes after ER of a RYGB in patients (age ≥ 18) with severe protein-calorie malnutrition from a single academic health center in Minneapolis, Minnesota over a seven-year period (2015-2021) were retrospectively reviewed pre-procedurally, and at six and twelve months post-procedurally. 17 patients underwent ER for severe protein-calorie malnutrition, or dependence on tube feeds (TF) or total parenteral nutrition (TPN). At 6 months post-ER, two patients were no longer malnourished and only on oral nutrition; three patients were liberated from TPN. Laboratory markers of protein-calorie malnutrition, renal function, and micronutrients were not significantly different at six- or twelve-month follow-up (P > 0.05). In all patients, access to the gastric remnant was maintained via stent placement through the gastric pouch or proximal Roux limb throughout the study period and no complications were noted after ER. Despite the small sample size, this investigation revealed that ER of RYGB may prevent progressive deleterious weight loss, and worsening macro- and micro-nutrient deficiencies, though improvement in weight and nutritional parameters was not observed. Overall, ER was found to be a nuanced and safe, advanced technique useful for when remnant access is desired in RYGB patients.